Closing the gap: accelerating the translational process in nanomedicine by proposing standardized characterization techniques - Khorasani AA (Dove Medical Press, 2014)
Ali A Khorasani,1–3 James L Weaver,4 Carolina Salvador-Morales2,3 1Department of Chemistry and Biochemistry, 2Bioengineering Department, 3Krasnow Institute for Advanced Study, George Mason University, Fairfax, VA, USA; 4Division of Applied Regulatory Science, Center for Drug Evaluation and Research, Food and Drug Administration, Silver Spring, MD, USA Abstract: On the cusp of widespread permeation of nanomedicine, academia, industry, and government have invested substantial financial resources in developing new ways to better treat diseases. Materials have unique physical and chemical properties at the nanoscale compared with their bulk or small-molecule analogs. These unique properties have been greatly advantageous in providing innovative solutions for medical treatments at the bench level. However, nanomedicine research has not yet fully permeated the clinical setting because of several limitations. Among these limitations are the lack of universal standards for characterizing nanomaterials and the limited knowledge that we possess regarding the interactions between nanomaterials and biological entities such as proteins. In this review, we report on recent developments in the characterization of nanomaterials as well as the newest information about the interactions between nanomaterials and proteins in the human body. We propose a standard set of techniques for universal characterization of nanomaterials. We also address relevant regulatory issues involved in the translational process for the development of drug molecules and drug delivery systems. Adherence and refinement of a universal standard in nanomaterial characterization as well as the acquisition of a deeper understanding of nanomaterials and proteins will likely accelerate the use of nanomedicine in common practice to a great extent. Keywords: physicochemical characterization, poly(ethylene glycol), protein adsorption, regulatory issues